2010
DOI: 10.1097/icl.0b013e3181efa61b
|View full text |Cite
|
Sign up to set email alerts
|

Postmarket Surveillance of Menicon Z Rigid Gas-Permeable Contact Lenses for up to 30 Days Continuous Wear in the United States

Abstract: On the basis of this study, CW of the Menicon Z hyper-Dk/t RGP lens provides a safe and full-time vision correction alternative for patients who can adapt to RGP lens wear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Even in 12-month studies in which CLs and supplies are provided free of charge, combined discontinuation and loss to follow-up rates between 32% and 36% have been reported. 9,14,27 The TEMPO Registry's retention at 82.3% is also slightly better than the 80% reported in a similarly designed study that was carried out a decade ago, 5,6 most likely due to improved ability to contact wearers electronically and allow them to submit their responses online. The registry encountered so few CIE events that our planned regression analysis to determine risk factors was not very fruitful.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Even in 12-month studies in which CLs and supplies are provided free of charge, combined discontinuation and loss to follow-up rates between 32% and 36% have been reported. 9,14,27 The TEMPO Registry's retention at 82.3% is also slightly better than the 80% reported in a similarly designed study that was carried out a decade ago, 5,6 most likely due to improved ability to contact wearers electronically and allow them to submit their responses online. The registry encountered so few CIE events that our planned regression analysis to determine risk factors was not very fruitful.…”
Section: Discussionmentioning
confidence: 57%
“…24 Postmarket surveillance is not typically required for CLs, but can be mandated under the FDA 522 guidelines. 25,26 In recent history, active postmarketing surveillance was mandated for three manufacturers of CLs that carried an indication for 30 nights of continuous wear 6,27 and for lenses that were used primarily by pediatric populations. 28 Occasionally, these mandates follow the publication of case reports from the literature indicating a safety concern during normal clinical use, as in the case of overnight orthokeratology.…”
mentioning
confidence: 99%
“…To address these issues, current rigid lenses are the rigid‐gas‐permeable (RGP) lenses made up of, for example, silicone acrylates or fluoro‐silicone/acrylate, which combined the advantages of both silicone (oxygen permeability) and PMMA (accessible manufacture) 14 . In 2010, Menicon Z contact lenses were the only rigid lenses that received FDA's approval for 30 days of continuous usage 15 . Compared to rigid lenes, soft lenses are more comfortable and have higher flexibility.…”
Section: Properties and Classification Of Contact Lensmentioning
confidence: 99%
“…[2][3][4][5][6][7] Table 3 shows the details from those FDA-mandated postapproval studies that generally found no change in the rate of microbial keratitis in the silicone hydrogel lenses with 30 nights of wear compared with hydrogels with 7 nights of overnight wear and an undetectable rate of microbial keratitis in the smaller RGP study. Its searchable database content is described on the FDA website thus: "MAUDE data represents reports of adverse events involving medical devices.…”
mentioning
confidence: 99%